The Civil Responsibility of CNC Machined Aftermarket of Motorcycle Rim Manufacturers Regarding Manufacturing Defects - Arrajab, Muhammad Baits; Kaharuddin, Kaharuddin (Law Development Journal, 2025)
This study examines the form of civil responsibility of CNC aftermarket rims manufacturers when their products are found to have manufacturing defects. This study focuses on the extent to which manufacturers are obliged to guarantee the safety of consumers regarding the products they produce. The method used in this study is a normative juridical approach, examining the legal provisions governing the relationship between manufacturers and consumers by reviewing how these rules are applied in the automotive industry. The findings of the study show that manufacturers must have both legal and ethical responsibilities to provide products that are safe and meet standards, and are obliged to compensate for losses arising from product defects. This paper is expected to serve as a reference for manufacturers and consumers in understanding the scope of each party's rights and obligations.